High-resolution CO images of the Galactic central molecular zone. (19th February 2019) - Tokuyama, Sekito; Oka, Tomoharu; Takekawa, Shunya; Iwata, Yuhei; Tsujimoto, Shiho; Yamada, Masaya; Furusawa, Maiko; Nomura, Mariko
Abstract: We performed Nyquist-sampled mapping observations of the central molecular zone of our Galaxy in the J = 1–0 lines of CO, 13 CO, and C 18 O using the 45 m telescope at the Nobeyama Radio Observatory. The newly obtained data sets were an improvement by a factor of four in spatial resolution of the CO data previously obtained with the same telescope 22 years ago, providing the highest angular resolution CO atlas of this special area of the Galaxy. The data cover the area: −0^°_. 8 ≤ l ≤ +1^°_. 4 and −0^°_. 35 ≤ b ≤ +0^°_. 35 with a 15″ beamwidth. Total intensity ratios for CO J = 3–2/ J = 1–0, 13 CO/CO J = 1–0 and C 18 O/ 13 CO J = 1–0, are 0.70 ± 0.06, 0.12 ± 0.01, and 0.14 ± 0.01, respectively. The high-resolution CO images show the fine structure of the molecular gas and enable us to identify a number of compact clouds with broad velocity widths, i.e., high-velocity compact clouds. We conducted a detailed comparison of our CO J = 1–0 data with the CO J = 3–2 data obtained with the James Clerk Maxwell Telescope to derive the distribution and kinematics of the highly excited gas. Three, out of four, of the previously identified high CO J = 3–2/ J = 1–0 ratio areas at l = +1^°_. 3, 0^°_. 0, and −0^°_. 4 were confirmed with a higher spatial resolution. In addition to these, we identified several very compact, high CO J = 3–2/ J = 1–0 spots with broad velocity widths for the first time. These are candidates for accelerated gas in the vicinity of invisible, point-like massive objects.